Impact of vacuum cleaning on indoor air quality. (August 2020) - Vicente, Estela D.; Vicente, Ana M.; Evtyugina, Margarita; Calvo, Ana I.; Oduber, Fernanda; Blanco Alegre, Carlos; Castro, Amaya; Fraile, Roberto; Nunes, Teresa; Lucarelli, Franco; Calzolai, Giulia; Nava, Silvia; et al.
Abstract: Vacuum cleaning can be a household source of particulate matter (PM) both from the vacuum motor and from settled dust resuspension. Despite the evidence of this contribution to PM levels indoors, the effect of this source on PM composition is still unknown. In this study, four vacuum cleaners (washable filter bag less, wet, bagged and HEPA filter equipped robot) were tested for the emission rate of particulate mass and number. The detailed PM chemical characterisation included organic and elemental carbon, metals and organic speciation. PM10 emission rates from bagged vacuum operation were much higher (207 ± 99.0 μg min −1 ) compared with the ones obtained from wet (86.1 ± 16.9 μg min −1 ) and washable filter bag less vacuums (75.4 ± 7.89 μg min −1 ). Particle (8–322 nm) number emission rates ranged from 5.29 × 10 11 (washable filter bag less vacuum) to 21.2 × 10 11 (wet vacuum) particles min −1 . Ratios of peak to background levels indicate that vacuuming can elevate the ultrafine particle number concentrations by a factor ranging from 4 to 61. No increase in PM mass or number concentrations was observed during the HEPA filter equipped vacuum operation. The increase in copper and elemental carbon PM10 contents during vacuuming suggested motor emissions. Organic compounds in PM10 included alkanes, PAHs, saccharides, phenolics, alcohols, acids, among others. However, it was not possible to establish a relationship between these compounds and vacuuming due to the vast array of possible household sources. The cancer risks associated with metals and PAH inhalation were negligible. Highlights: Vacuum cleaner type had a great effect on PM mass and number emissions. HEPA filters can significantly reduce the PM emitted by the vacuum cleaner motor. Elemental carbon increased markedly during the operation of wet and bagged vacuums. Cooper enrichment factors were high when using vacuum cleaners without HEPA filter. The inhalation cancer risk for metals and PAHs was negligible.